DEVELOPMENT OF LOCAL ALLOMETRIC EQUATION TO ESTIMATE TOTAL ABOVEGROUND BIOMASS IN PAPUA TROPICAL FOREST - Maulana, Sandhi I.; Wibisono, Yohannes; Utomo, Singgih (Indonesian Journal of Forestry Research, 2016)
Recently, pantropical allometric equations have been commonly used across the globe to estimate the aboveground biomass of the forests, including in Indonesia. However, in relation to regional differences in diameter, height and wood density, the lack of data measured, particularly from eastern part of Indonesia, may raise the question on accuracy of pantropical allometric in such area. Hence, this paper examines the differences of local allometric equations of Papua Island with equations developed by Chave and his research groups. Measurements of biomass in this study were conducted directly based on weighing and destructive samplings. Results show that the most appropriate local equation to estimate total aboveground biomass in Papua tropical forest is Log(TAGB) = -0.267 + 2.23 Log(DBH) +0.649 Log(WD) (CF=1.013; VIF=1.6; R2= 95%; R2-adj= 95.1%; RMSE= 0.149; P<0.001). This equation is also a better option in comparison to those of previously published pantropical equations with only 6.47% average deviation and 5.37 points of relative bias. This finding implies that the locally developed equation should be a better option to produce more accurate site specific total aboveground biomass estimation.